Interleukin-3 Inhibition Regulate Inflammation and Tissue Damage in Acute Pancreatitis - Merza, Mohammed; Taufiq, Govand; Othman, Banw Anwar; Ahmad, Kewan Kamal (Journal of Neonatal Surgery, 2025)
Background and Objective: Acute Pancreatitis (AP) is associated with leukocyte infiltration and tissue necrosis; however, the underlying cellular signaling pathways leading to organ damage remain unclear. IL-3 is a key regulator of various cellular processes that drive pro-inflammatory responses. This study aims to investigate the role of IL-3 signaling in acute pancreatitis. Methods: Pancreatitis was induced in C57BL/6 mice using intraperitoneal L-arginine injection. Prior to the onset of pancreatitis, animals received an IL-3 inhibitor (100 mg/kg). The levels of Interleukin 6, myeloperoxidase, and macrophage inflammatory protein 2 were assessed using the enzyme-linked immunosorbent assay. Results: IL-3 administration significantly reduced the L-arginine-induced increase in serum lipase, pancreatic neutrophil infiltration, pancreatic edema, and acinar cell necrosis. Additionally, IL-3 inhibition led to a significant decrease in myeloperoxidase levels in both the pancreas and lungs following L-arginine exposure (P<0.05). However, IL-3 treatment notably influenced L-arginine-induced macrophage inflammatory protein-2 (MIP-2) expression in the pancreas. Interestingly, in vivo neutrophil isolation demonstrated that IL-3 inhibition significantly reduced macrophage inflammatory protein 2 and IL-6 levels, suggesting a direct role of IL-3 in modulating chemokine and cytokine expression in neutrophils (P<0.05). Lastly, IL-3 inhibition did not directly impact secretagogue-induced trypsinogen activation in pancreatic acinar cells in vitro (P>0.05). Conclusion: These findings highlight the crucial role of IL-3 signaling in acute pancreatitis by regulating tissue damage and neutrophil infiltration. Beyond advancing the understanding of pancreatitis signaling mechanisms, this study suggests that IL-3 may serve as a potential therapeutic target for severe AP.